Australian Political Institutions - AITKIN, Don (Longman Cheshire, 1989)
Australian Political Institutions 10e introduces students to the structure and organisation of the institutions and functions of government in Australia, with reference to contemporary issues and debates. A lot has changed in recent times in the Australian political environment. Finally there is a text that incorporates all these important changes. As an introduction to the principles of political science the text provides an analysis of key issues in the Australian political system in a clear and concise manner. This new tenth edition retains its core focus on the Australian political system but also includes expanded comparative analysis of the similarities and differences in the structure and operation of political institutions in other countries which students can use to consider the strengths and weaknesses of the Australian political system and whether it could be improved